Natural convection in a representative section of an ONAN distribution transformer - Córdoba, Paola A. (2017)
We present a 3D numerical modeling of an ONAN distribution transformer. We found that the 3D problem of natural convection in this thermohidraulic device can be studied by a numerical model that represents a 3D slice of an ONAN distribution transformer. The numerical study was carried out by applying the Finite Element Method to solve the 3D Navier-Stokes and heat equations using the in-house developed Par-GPFEP code. We compared the present results with those of other authors who used a similar approach with some differences in the solution method and in the simplifications considered. Also we compared the numerical temperature distribution with thermographies presented in a heating test performed in an ONAN transformer provided by Tubos Trans Electric S.A. The numerical results are also compared with velocity fields measurements taken in an experimental device that was built to simulate a representative slice of the transformer of interest. A PIV setup was used to obtain the flow velocity field. We found reasonable agreement between numerical and the preliminary experimental results, showing stratified temperature distributions and similar flow patterns in the studied region.